High-strength and high-conductivity graphene / copper composite material and preparation method
Through the combination of chemical peeling method and hydrothermal method, the problems of complex and high cost of graphene/copper composite preparation process are solved, and high-efficiency and low-cost high-strength and high-conducting materials are achieved, forming a uniform three-dimensional interconnection structure, which is improved. Mechanical and electrical conductivity of materials.
Patent Information
- Application Number
- CN202411032838.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-30
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-07-30
AI Technical Summary
The preparation process of existing graphene/copper composites is complex, and it is difficult to achieve industrialization with high temperature sintering, and it is difficult to achieve uniform mixing and agglomeration of the additive methods, resulting in high industrialization, high cost, and reduced conductivity.
The chemical peeling method and the hydrothermal method are combined to allow DMF to enter the interlayer of graphite powder and peel it into graphene oxide through hydrothermal reaction. The binder organic matter enhances the binding force between graphene oxide and copper powder, prevents agglomeration, and passes through a reducing atmosphere. The uniform graphene/copper composite was formed with vacuum hot pressing.
It realizes the low-cost and efficient preparation of high-strength high-conducting graphene/copper composite materials, simplifies the process flow, reduces costs, improves the mechanical properties and conductivity of the materials, forms a three-dimensional connected structure, and enhances the overall mechanical properties and conductivity.
Smart Images

Figure CN119120968A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of industrialized mass production process of graphene / copper composite materials, and in particular to a method for preparing a high-strength and high-conductivity graphene / copper composite material. Background Art
[0002] Graphene is considered to be the most promising reinforcing material in copper-based composites because of its excellent mechanical and physical properties and a specific surface area of 2630 m 2 ·g -1 , high electron mobility reaches 200,000cm 2 ·v -1 ·s -1 , high Young's modulus reaches 1.0TPa and thermal conductivity reaches 5000W·m -1 ·K -1 .
[0003] In recent years, many scholars have conducted extensive research on the composite of graphene and metal. After graphene is introduced into copper, aluminum and other substrates, the performance of the material can be effectively improved, and the prepared composite material has high strength, high thermal conductivity, high electrical conductivity, low friction coefficient, etc. It can be used for electrical contact materials, packaging materials, wear-resistant materials and corrosion-resistant materials, etc., and has potential application value in many fields.
[0004] There are generally two ways to combine graphene with copper.
[0005] The first is in-situ growth. For example, in the paper Adv.Funct.Mater.2019,29,1806792, Zhang Di's team from Shanghai Jiaotong University obtained graphene / copper foil by chemical vapor deposition (CVD), and then hot-pressed it into a layered composite material to obtain a graphene / copper product with a high conductivity of 117% IACS. In the paper Carbon.2022,186:303-312, Gao Zhaoshun's team from the Institute of Electrical Engineering of the Chinese Academy of Sciences used a liquid carbon source combined with hot pressing and sintering to generate graphene in situ. The mechanical properties of the composite material were greatly improved, but the conductivity was slightly reduced.
[0006] The second is an external addition method: graphene powder or graphite is mixed with copper and directly added to the inside of the copper or coated on the surface. For example, in patent CN202110851980.6, Yang Zhenyu proposed a graphene / copper wire and a preparation method thereof. After mixing a few layers of graphene oxide powder and oxygen-free copper powder, they were hot-pressed and sintered at low temperature, and then auxiliary materials were added for vacuum melting to obtain a graphene / copper composite material with a volume content of more than 99.99%. The thermal conductivity can reach 500-600W / m·K, and the volume resistivity is reduced by 5-20%. In the paper Composites Part B: Engineering, 2021, 216: 108850, Chen used graphite and copper for multiple rolling to prepare graphene / copper composite materials. Although the conductivity has decreased to a certain extent (68% IACS), the mechanical properties have been greatly improved.
[0007] The graphene / copper composite materials prepared by the in-situ growth method have a complete graphene structure with few defects, and the graphene is tightly bonded to the copper substrate surface. However, they require high temperatures close to 1000°C, and the carbonization and sintering processes are very cumbersome, which greatly limits the application of this method and makes it difficult to industrialize.
[0008] It is difficult to achieve uniform mixing of graphene and copper by the external addition method, which easily leads to agglomeration. In particular, the graphene floating phenomenon is serious during the smelting process and the process is complicated, so it is not conducive to mass production.
[0009] At present, there are few reports on the direct preparation of graphene / copper composites from graphite by hydrothermal reduction. Most researchers use one-time hydrothermal synthesis to obtain CuO / graphene oxide (GO or RGO) composites, and a small number of other researchers obtain graphene / copper composites, but their raw materials are all graphene oxide instead of simpler, easier to obtain and lower cost graphite. Summary of the invention
[0010] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing high-strength and high-conductivity graphene / copper composite materials, which effectively uses low-cost graphite to achieve industrial mass production of graphene / copper composite materials, has a shorter preparation process, higher preparation efficiency, lower industrial mass production cost, and more energy saving and consumption reduction, and has many technical advantages.
[0011] In order to achieve the above object, the technical solution adopted by the present invention is:
[0012] A method for preparing a high-strength and high-conductivity graphene / copper composite material, which is prepared by combining a chemical exfoliation method with a hydrothermal method, includes the following preparation steps and preparation conditions:
[0013] Step S1, weighing copper powder and graphite powder according to a weight ratio to obtain a mixed powder, wherein the mass ratio of the copper powder to the graphite powder is 1:0.01-0.03, adding alcohol to the mixed powder, and mixing uniformly to obtain a mixture;
[0014] Step S2, preparing a mixed solution, sealing and stirring the binder organic matter and the solvent to prepare a mixed solution, the binder organic matter is selected from alcohols, the solvent is selected from at least one of DMF and NMP, the weight ratio of the binder organic matter to the solvent is 1:5-10, and the total mass of the mixed solution accounts for 10-20%;
[0015] Step S3, transferring the mixture of step 1 and the mixed solution of step S2 into a hydrothermal reaction kettle, controlling the temperature in the hydrothermal kettle at 150° C. to 220° C., performing a hydrothermal reaction for 5 to 30 hours, and waiting for the hydrothermal reaction kettle to cool to room temperature after the hydrothermal reaction is completed to obtain a graphene oxide-coated copper powder composite material;
[0016] Among them, DMF uses the high temperature and high pressure of the hydrothermal reaction to enter the graphite intercalation layer of the graphite powder and peel the graphite into graphene oxide.
[0017] The binder organic matter uses the high temperature and high pressure of the hydrothermal reaction to make the oxygen-containing groups on the surface of the formed graphene oxide generate hydrogen bonds or weak interactions with the surface of the copper powder.
[0018] The bonding force between graphene oxide and copper powder is enhanced by the binder organic matter, and the copper powder and graphene oxide are effectively dispersed. At the same time, the binder organic matter is used to prevent the graphene oxide from agglomerating, so that the graphene oxide is closely attached to the surface of the copper powder and evenly coated on the surface of the copper powder.
[0019] The surface of the copper powder is uniformly coated with a graphene oxide film having 3 to 5 layers of graphene oxide and a sheet-like film structure without generating gaps, so as to form the graphene oxide-coated copper powder composite material;
[0020] Step S4, filtering, washing and vacuum drying the graphene oxide-coated copper powder composite material of step S3 in sequence to obtain a pure graphene oxide-coated copper powder composite material;
[0021] Step S5, using a reducing atmosphere to perform a reduction reaction on the graphene oxide-coated copper powder composite material, the reduction temperature is 200-450° C., the reduction reaction time is 1-3 hours, the graphene oxide coated on the surface of the copper powder is reduced to graphene, and the copper powder surface is uniformly coated with 3-5 layers of graphene and a graphene / copper composite material with a flaky film structure is obtained;
[0022] Step S6, vacuum hot pressing the graphene / copper composite material of step S5 to obtain a graphene / copper block, the graphene / copper block presents Cu(111), Cu(200) and Cu(220) crystal plane indices, exhibits a polycrystalline copper structure, and the bulk conductivity of the graphene / copper block is 97-107% IACS.
[0023] In a further technical solution, in step S6, after the copper powder completely coated with graphene is subjected to hot pressing treatment, the graphene located between the copper powder particles is interconnected and presents a three-dimensional connected structure in the block, and the surface of the graphene / copper block obtained by hot pressing treatment has no pores or holes.
[0024] In a further technical solution, the purity of the copper powder is greater than 99.9%, the particle size of the copper powder is 15 μm-50 μm, and the input weight of the copper powder is 97-99% of the total weight of the raw materials composed of the mixed powder;
[0025] The particle size of the graphite powder is 20 μm-50 μm, and the input weight of the graphite powder is 1% to 3% of the total weight of the raw materials composed of the mixed powder;
[0026] The binder organic matter is selected from at least one of ethylene glycol, polypropylene glycol and polyethylene glycol, and the input weight of the binder organic matter is 10-20% of the total weight of the raw materials consisting of the mixture and the mixed solution.
[0027] In a further technical solution, in step S2, the binder organic substance is polyethylene glycol, the solvent is DMF, and the mass ratio of polyethylene glycol to DMF is 1:5-10;
[0028] In step S3, the oxygen-containing groups include hydroxyl groups and carboxyl groups;
[0029] In step S5, the reduction temperature of the reduction reaction is 250-450° C., the reduction reaction time is 0.5-1 hour, and the part of the graphene formed by the reduction reaction has wrinkles, and the Raman characteristic peak I of the graphene / copper composite material D / I G The ratio is 0.16-0.18.
[0030] In a further technical solution, in step S3, the temperature in the hydrothermal kettle is controlled at 180-190° C., and the hydrothermal reaction is carried out for 10-15 hours.
[0031] In step S5, the reduction temperature of the reduction reaction is 350° C. and maintained for 1 hour.
[0032] In step S6, the graphene / copper composite material is subjected to vacuum hot pressing at a temperature of 800° C. for 2 hours.
[0033] In a further technical solution, in step S5, a mixed gas of nitrogen and hydrogen is used as a reducing atmosphere, the volume percentage of hydrogen in the reducing atmosphere is 1-5%, the temperature of the reduction reaction of the graphene oxide-coated copper powder composite material is 300-600° C., and the reduction reaction time is 30-200 min;
[0034] In the step S6, the vacuum hot pressing temperature of the vacuum hot pressing treatment is 600° C.-1000° C., and the vacuum hot pressing time is 1-12 hours.
[0035] In a further technical solution, in step S5, the temperature for the reduction reaction of the graphene oxide-coated copper powder composite material is 350° C., and the reduction reaction time is 60 min;
[0036] In step S6, the vacuum hot pressing temperature of the vacuum hot pressing treatment is 800° C. and the vacuum hot pressing time is 2 hours; the periphery of the polycrystalline copper structure has 3-5 layers of graphene, and the graphene between each polycrystalline copper structure is interconnected to present a three-dimensional connected structure.
[0037] A high-strength and high-conductivity graphene / copper composite material, wherein the graphene / copper block exhibits a polycrystalline copper structure, presents Cu(111), Cu(200) and Cu(220) crystal plane indices, and has a bulk conductivity of 97-107% IACS. The periphery of the polycrystalline copper structure has 3-5 layers of graphene, and the graphene between each polycrystalline copper structure is interconnected and presents a three-dimensional interconnected structure. Part of the graphene located on the periphery of the polycrystalline copper structure has wrinkles, and the wrinkles are 6-8 layers of graphene.
[0038] Compared with the prior art, the present invention has the following advantages: the present invention effectively uses low-cost graphite to achieve industrial mass production of high-strength and high-conductivity graphene / copper composite materials, has a shorter preparation process, higher preparation efficiency, lower industrial mass production cost, more energy saving and consumption reduction, and has many technical advantages.
[0039] The present invention adds a small amount of graphite to the copper material, uses chemical stripping and high-pressure bonding to ensure uniform dispersion of graphene in the matrix, and achieves strong interface bonding with the matrix to form a three-dimensional interconnected graphene structure, which can effectively bear the load under the action of tensile stress and enhance the overall mechanical properties; the present invention enhances the charge transfer efficiency of the copper matrix through the three-dimensional graphene structure, gives full play to the role of the high conductivity of graphene, and makes the prepared copper-graphene composite material have high strength and high conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is a physical picture of the raw copper powder and the graphene-coated copper powder in the example.
[0041] Figure 2 This is the Raman graph of graphene oxide-coated copper powder prepared in the example.
[0042] Figure 3 This is the Raman image of graphene on the copper powder surface after reduction in the example.
[0043] Figure 4 This is a real optical microscope image of graphene-coated copper powder in the embodiment.
[0044] Figure 5 This is a photo of the hot-pressed graphene / copper block in the example.
[0045] Figure 6 This is the XRD pattern of the graphene / copper bulk prepared in Example 1. DETAILED DESCRIPTION
[0046] A method for preparing a high-strength and high-conductivity graphene / copper composite material, which is prepared by combining a chemical exfoliation method with a hydrothermal method, includes the following preparation steps and preparation conditions:
[0047] Step S1, weighing copper powder and graphite powder according to a weight ratio to obtain a mixed powder, wherein the mass ratio of the copper powder to the graphite powder is 1:0.01-0.03, adding alcohol to the mixed powder, and mixing uniformly to obtain a mixture;
[0048] The purity of the copper powder is greater than 99.9%, the particle size of the copper powder is 15 μm-50 μm, and the input weight of the copper powder is 97-99% of the total weight of the mixed powder;
[0049] The particle size of the graphite powder is 20 μm-50 μm, and the input weight of the graphite powder is 1% to 3% of the total weight of the raw materials composed of the mixed powder.
[0050] Step S2, preparing a mixed solution, the binder organic matter and the solvent are sealed and stirred to prepare a mixed solution, the binder organic matter is selected from alcohols, the solvent is selected from at least one of DMF and NMP, the weight ratio of the binder organic matter to the solvent is 1:5-10, and the total mass concentration of the mixed solution is 10-20%;
[0051] DMF is the chemical abbreviation of dimethylformamide (N,N-Dimethylformamide), and NMP is the chemical abbreviation of N-methyl-2-pyrrolidone. Preferably, the binder organic matter is polyethylene glycol, and the solvent is DMF, and the mass ratio of polyethylene glycol to DMF is 1:5-10.
[0052] The binder organic matter is selected from at least one of ethylene glycol, polypropylene glycol and polyethylene glycol, and the input weight of the binder organic matter is 10-20% of the total mass of the mixed solution.
[0053] Step S3, transferring the mixture of step 1 and the mixed solution of step S2 into a hydrothermal reaction kettle, controlling the temperature in the hydrothermal kettle at 150°C to 220°C, and performing the hydrothermal reaction for 5 to 30 hours, preferably, controlling the temperature in the hydrothermal kettle at 180 to 190°C, and performing the hydrothermal reaction for 10 to 15 hours. After the hydrothermal reaction is completed, waiting for the hydrothermal reaction kettle to cool to room temperature, to obtain a graphene oxide-coated copper powder composite material;
[0054] Among them, DMF uses the high temperature and high pressure of the hydrothermal reaction to enter the graphite intercalation layer of the graphite powder and peel the graphite into graphene oxide.
[0055] The binder organic matter uses the high temperature and high pressure of the hydrothermal reaction to make the oxygen-containing groups (hydroxyl and carboxyl) on the surface of the formed graphene oxide produce hydrogen bonds or weak interactions with the surface of the copper powder, thereby enhancing the bonding force between the graphene oxide and the copper powder, and can effectively disperse the copper powder and graphene oxide and prevent them from agglomerating, while helping to form a uniform composite material and improving the bonding effect between the graphene oxide and the copper powder.
[0056] The bonding force between graphene oxide and copper powder is enhanced by the binder organic matter, and the copper powder and graphene oxide are effectively dispersed. At the same time, the binder organic matter is used to prevent the graphene oxide from agglomerating, so that the graphene oxide is closely attached to the surface of the copper powder and evenly coated on the surface of the copper powder.
[0057] The use of polyethylene glycol helps the graphene oxide to combine with the surface of the copper powder and form a dense structure, and the graphene oxide is closely attached to the surface of the copper powder without generating gaps, so that the surface of the copper powder is evenly coated with a graphene oxide film having 3 to 5 layers of graphene oxide and a flaky film structure without generating gaps, so as to form the graphene oxide-coated copper powder composite material;
[0058] Using a hydrothermal reactor container for high temperature and high pressure reaction can make graphene oxide deposit on the copper powder, so that the distribution of graphene oxide is more uniform. The surface of the copper powder is black before reduction, indicating that the copper powder is completely covered and the color of the copper itself is not revealed. Figure 1 As shown, its surface Raman characteristic peaks are as follows Figure 2 shown.
[0059] Step S4, filtering, washing and vacuum drying the graphene oxide-coated copper powder composite material of step S3 in sequence to obtain a pure graphene oxide-coated copper powder composite material;
[0060] Step S5, using a reducing atmosphere to perform a reduction reaction on the graphene oxide coated copper powder composite material, using a mixed gas formed by a mixture of nitrogen and hydrogen as the reducing atmosphere, the volume percentage of hydrogen in the reducing atmosphere is 1-5%, the temperature for the reduction reaction of the graphene oxide coated copper powder composite material is 300-600° C., and the reduction reaction time is 30-200 min. Preferably, the reduction temperature is controlled at 200-450° C., and the reduction reaction time is controlled at 1-3 hours. The graphene oxide coated on the surface of the copper powder is reduced to graphene, and a graphene / copper composite material having a flaky film structure and 3-5 layers of graphene uniformly coated on the surface of the copper powder is obtained;
[0061] The present invention reduces graphene oxide to graphene through a reduction reaction, and removes all organic solvents, so that no impurities remain on the contact surface between graphene and copper, thereby not affecting physical properties.
[0062] Among them, the temperature of the thermal reduction reaction cannot be too high, the reduction temperature is 250-450°C, and cannot exceed 500°C. The reduction reaction time is 0.5 to 1 hour. If the temperature is too high, the graphene will react in the hydrogen atmosphere and be etched in large quantities, leaving exposed copper powder particles. The copper powders will stick together, affecting the subsequent hot pressing process. In particular, the copper powder surface will stick together, which will cause holes and gaps between the copper-copper interface. The presence of gaps will have a huge impact on electrical conductivity and thermal conductivity. When the temperature is low, organic residues are likely to be generated, and a longer heat treatment time is required, which increases the cost. Preferably, the reduction temperature is 350°C and maintained for 1 hour. Part of the graphene formed by the reduction reaction has wrinkles, and the Raman characteristic peak I of the graphene / copper composite material D / I G The ratio is 0.16-0.18. After the vacuum hot pressing treatment in step S6, a graphene / copper block with a thermal conductivity of 496 W / (m·K), an electrical conductivity of 106.8% IACS, and a tensile strength of 521 MPa is obtained.
[0063] Step S6, vacuum hot pressing the graphene / copper composite material of step S5, wherein the vacuum hot pressing temperature of the vacuum hot pressing treatment is 600°C-1000°C, and the vacuum hot pressing time is 1-12 hours. Preferably, the vacuum hot pressing temperature is 800°C, and the vacuum hot pressing time is 2 hours, to obtain a graphene / copper block. The graphene / copper block obtained after hot pressing is metallic yellow, as shown in the attached Figure 5 As shown, the macroscopic photograph shows that there are no pores and holes on the surface of the sample after hot pressing.
[0064] After the copper powder completely covered by graphene is hot-pressed, the graphene between the copper powder particles is connected to each other and presents a three-dimensional interconnected structure in the block. The surface of the graphene / copper block obtained by hot-pressing has no pores and holes. The XRD of the hot-pressed graphene / copper block is as shown in the attached figure. Figure 6 As shown in the figure, the graphene / copper bulk exhibits Cu(111), Cu(200) and Cu(220) crystal plane indices, showing a polycrystalline copper structure. The bulk conductivity of the graphene / copper bulk is 97-107% IACS. The graphene is well coated on the surface of the copper powder, and there is no adhesion between the copper powders. The graphene is in the form of flakes and particles and the reduced oxide graphene is well coated. Figure 4 shown.
[0065] A high-strength and high-conductivity graphene / copper composite material is prepared according to the above method. The graphene / copper block exhibits a polycrystalline copper structure, presents Cu(111), Cu(200) and Cu(220) crystal plane indices, and the bulk conductivity of the graphene / copper block is 97-107% IACS. The periphery of the polycrystalline copper structure has 3-5 layers of graphene, and the graphene between each polycrystalline copper structure is interconnected and presents a three-dimensional interconnected structure. Part of the graphene located on the periphery of the polycrystalline copper structure has wrinkles, and the wrinkles are graphene with 6-8 layers.
[0066] Among them, the content of graphite should be appropriate. Too high a graphite content will cause too much graphene oxide film to be deposited on the surface of the copper powder and produce more wrinkles or stack into a thick film, thereby causing agglomeration. Especially for graphene oxide layers with a thickness of more than 10 layers, it is not conducive to improving the conductive performance.
[0067] When the graphite content is low, the graphene oxide film peeled off will be less, and the less monolayer graphene oxide will cause the coverage of the graphene oxide on the surface of the copper powder to be insufficient, and the copper powder surface cannot be completely coated, and the pure part of the copper powder surface will be exposed, which will cause the copper-copper interface to contact and diffuse with each other during the hot pressing process and metallurgical bonding will occur, which will eventually lead to the inability to form a three-dimensional interconnected structure of graphene, which is not conducive to the conduction characteristics of the graphene interface, and is not conducive to the improvement of overall electrical conductivity. Preferably, it is optimal to add 1.5g of graphite per 100.0g of copper powder, and the thickness of the corresponding graphene oxide film is 3-5 layers. After heat treatment reduction, the graphene formed by reduction completely coats the copper powder, and there is no metallic copper exposed. The powder color is close to that of pure copper powder and is metallic yellow. The number of graphene layers on the surface of the copper powder is mainly 3-5 layers, and it is coated on the surface of the copper powder in a sheet-like film structure. Some graphene has certain wrinkles, and the Raman characteristic peak I D / I G The ratio is about 0.17.
[0068] Example 1
[0069] Weigh 100.0 g of copper powder and add it to a 250 mL beaker, add 1 g of graphite; then add polyethylene glycol and DMF, the ratio of polyethylene glycol to DMF is 1:5, and the mass is 20 g.
[0070] The beaker was placed in a constant temperature water bath, maintained at 45°C, and then placed in a hydrothermal kettle for reaction at 160°C for 12 hours. After the reactor was cooled to room temperature, it was filtered, washed, and vacuum dried in sequence, and then placed in a mixture of argon and hydrogen for heat treatment at 350°C for 1 hour.
[0071] A mixed gas of nitrogen and hydrogen is used as a reducing atmosphere to perform a reduction reaction, the reduction reaction temperature is 350°C and maintained for 1 hour, and then a vacuum hot pressing treatment is performed on it, the vacuum hot pressing temperature is 800°C and the time is 2 hours, to obtain a graphene / copper composite material.
[0072] The thermal conductivity of the material measured by experimental instruments is 380W / (m·K), the electrical conductivity is 103.3%IACS, and the tensile strength is 410MPa.
[0073] Example 2
[0074] Weigh 100.0 g of copper powder and add it to a 250 mL beaker, add 2 g of graphite; then add polyethylene glycol and DMF, the ratio of polyethylene glycol to DMF is 1:5, and the mass is 20 g.
[0075] The beaker was placed in a constant temperature water bath, maintained at 45°C, and then placed in a hydrothermal kettle for reaction at 160°C for 12 hours. After the reactor was cooled to room temperature, it was filtered, washed, and vacuum dried in sequence, and then placed in a mixture of argon and hydrogen for heat treatment at 350°C for 1 hour.
[0076] A mixed gas of nitrogen and hydrogen is used as a reducing atmosphere to carry out a reduction reaction. The reduction reaction temperature is 350°C and maintained for 1 hour. Then, a vacuum hot pressing treatment is carried out. The vacuum hot pressing temperature is 800°C and the time is 2 hours to obtain a graphene / copper composite material.
[0077] The thermal conductivity of the material was measured to be 455 W / (m·K), the electrical conductivity was 102.6% IACS, and the tensile strength was 432 MPa.
[0078] Example 3
[0079] Weigh 100.0 g of copper powder and add it to a 250 mL beaker, add 1.5 g of graphite; then add polyethylene glycol and DMF, the ratio of polyethylene glycol to DMF is 1:5, and the mass is 20 g.
[0080] The beaker was placed in a constant temperature water bath, maintained at 45°C, and then placed in a hydrothermal kettle for reaction at 160°C for 12 hours. After the reactor was cooled to room temperature, it was filtered, washed, and vacuum dried in sequence, and then placed in a mixture of argon and hydrogen for heat treatment at 350°C for 1 hour.
[0081] A mixed gas of nitrogen and hydrogen is used as a reducing atmosphere to carry out a reduction reaction. The reduction reaction temperature is 350°C and maintained for 1 hour. Then, a vacuum hot pressing treatment is carried out. The vacuum hot pressing temperature is 800°C and the time is 2 hours to obtain a graphene / copper composite material.
[0082] The thermal conductivity of the material was measured to be 496 W / (m·K), the electrical conductivity was 106.8% IACS, and the tensile strength was 521 MPa.
[0083] Example 4
[0084] Weigh 100.0 g of copper powder into a 250 mL beaker, add 3 g of graphite; then add polyethylene glycol and DMF, the ratio of polyethylene glycol to DMF is 1:5, and the mass is 20 g.
[0085] The beaker was placed in a constant temperature water bath, maintained at 45°C, and then placed in a hydrothermal kettle for reaction at 160°C for 12 hours. After the reactor was cooled to room temperature, it was filtered, washed, and vacuum dried in sequence, and then placed in a mixture of argon and hydrogen for heat treatment at 350°C for 1 hour.
[0086] A mixed gas of nitrogen and hydrogen is used as a reducing atmosphere to carry out a reduction reaction. The reduction reaction temperature is 350°C and maintained for 1 hour. Then, a vacuum hot pressing treatment is carried out. The vacuum hot pressing temperature is 800°C and the time is 2 hours to obtain a graphene / copper composite material.
[0087] The thermal conductivity of the material was measured to be 56 W / (m·K), the electrical conductivity was 99.1% IACS, and the tensile strength was 473 MPa.
[0088] Example 5
[0089] Weigh 100.0 g of copper powder and add it to a 250 mL beaker; then add polyethylene glycol and DMF, the ratio of polyethylene glycol to DMF is 1:5, and the mass is 20 g.
[0090] The beaker was placed in a constant temperature water bath, maintained at 45°C, and then placed in a hydrothermal kettle for reaction at 160°C for 12 hours. After the reactor was cooled to room temperature, it was filtered, washed, and vacuum dried in sequence, and then placed in a mixture of argon and hydrogen for heat treatment at 350°C for 1 hour.
[0091] A mixed gas of nitrogen and hydrogen is used as a reducing atmosphere to perform a reduction reaction, the reduction reaction temperature is 350°C and maintained for 1 hour, and then a vacuum hot pressing treatment is performed on it, the vacuum hot pressing temperature is 800°C and the time is 2 hours, to obtain a graphene / copper composite material.
[0092] The thermal conductivity of the material measured by experimental instruments is 364W / (m·K), the electrical conductivity is 100.3%IACS, and the tensile strength is 376MPa.
[0093] Electrical conductivity (%IACS) Tensile strength(MPa) Thermal conductivity (W / (mK)) Example 1 103.3 410 380 Example 2 102.6 432 455 Example 3 106.8 521 496 Example 4 99.1 473 563 Example 5 100.3 376 364
[0094] Table 1-Material performance test comparison table
[0095] The test standards used in Table 1 are:
[0096] Tensile strength: The room temperature tensile test is carried out in accordance with GB / T228.1-2010 Metallic Materials Tensile Test Part 1: Room Temperature Test Method, and the tensile strength of the sample is tested on an electronic universal mechanical properties testing machine.
[0097] Conductivity: The conductivity of the test sample is measured by the volt-ampere method using the "GB / T32791-2016 Eddy Current Test Method for Electrical Conductivity of Copper and Copper Alloys" and a Keithley power supply voltmeter.
[0098] Thermal conductivity: Laser thermal conductivity meter tests thermal diffusion coefficient, and then calculates thermal conductivity based on the test specific heat and density. XRD is used to analyze the phase; Raman spectroscopy tests the surface material of copper powder; optical microscopy is used to analyze the surface morphology.
[0099] From the results analysis of the material performance test comparison table in Table 1, it can be seen that compared with the pure copper control group without graphite in Example 5, the graphene / copper composite material prepared by the hydrothermal method combined with reduction and hot pressing methods has higher electrical conductivity and thermal conductivity, and the synergistic enhancement of electrical conductivity, tensile strength and thermal conductivity is achieved in Examples 1 to 3.
[0100] The advantages of the above technical solution of the present invention are as follows:
[0101] (1) The present invention prepares a graphene / copper composite material using graphite and copper powder as raw materials by a hydrothermal method combined with reduction heat treatment, which provides a new idea for the preparation of graphene / copper composite materials.
[0102] (2) The preparation process of the present invention is simple, the reaction conditions are mild, and no high-temperature calcination is required.
[0103] (3) The maximum thermal conductivity of the prepared graphene / copper bulk is 496 W / (m·K), and the maximum electrical conductivity is 106.8% IACS.
Claims
1. A method for preparing a high-strength and high-conductivity graphene / copper composite material, characterized in that: The preparation is carried out by combining chemical exfoliation method with hydrothermal method, including the following preparation steps and preparation conditions: Step S1, weighing copper powder and graphite powder according to a weight ratio to obtain a mixed powder, wherein the mass ratio of the copper powder to the graphite powder is 1:0.01-0.03, adding alcohol to the mixed powder, and mixing uniformly to obtain a mixture; Step S2, preparing a mixed solution, sealing and stirring the binder organic matter and the solvent to prepare a mixed solution, the binder organic matter is selected from alcohols, the solvent is selected from at least one of DMF and NMP, the weight ratio of the binder organic matter to the solvent is 1:5-10, and the total mass of the mixed solution accounts for 10-20%; Step S3, transferring the mixture of step 1 and the mixed solution of step S2 into a hydrothermal reaction kettle, controlling the temperature in the hydrothermal kettle at 150° C. to 220° C., performing a hydrothermal reaction for 5 to 30 hours, and waiting for the hydrothermal reaction kettle to cool to room temperature after the hydrothermal reaction is completed to obtain a graphene oxide-coated copper powder composite material; Among them, DMF uses the high temperature and high pressure of the hydrothermal reaction to enter the graphite intercalation layer of the graphite powder and peel the graphite into graphene oxide. The binder organic matter uses the high temperature and high pressure of the hydrothermal reaction to make the oxygen-containing groups on the surface of the formed graphene oxide generate hydrogen bonds or weak interactions with the surface of the copper powder. The bonding force between graphene oxide and copper powder is enhanced by the binder organic matter, and the copper powder and graphene oxide are effectively dispersed. At the same time, the binder organic matter is used to prevent the graphene oxide from agglomerating, so that the graphene oxide is closely attached to the surface of the copper powder and evenly coated on the surface of the copper powder. The surface of the copper powder is uniformly coated with a graphene oxide film having 3 to 5 layers of graphene oxide and a sheet-like film structure without generating gaps, so as to form the graphene oxide-coated copper powder composite material; Step S4, filtering, washing and vacuum drying the graphene oxide-coated copper powder composite material of step S3 in sequence to obtain a pure graphene oxide-coated copper powder composite material; Step S5, using a reducing atmosphere to perform a reduction reaction on the graphene oxide-coated copper powder composite material, the reduction temperature is 200-450° C., the reduction reaction time is 1-3 hours, the graphene oxide coated on the surface of the copper powder is reduced to graphene, and the copper powder surface is uniformly coated with 3-5 layers of graphene and a graphene / copper composite material with a flaky film structure is obtained; Step S6, vacuum hot pressing the graphene / copper composite material of step S5 to obtain a graphene / copper block, the graphene / copper block presents Cu(111), Cu(200) and Cu(220) crystal plane indices, exhibits a polycrystalline copper structure, and the bulk conductivity of the graphene / copper block is 97-107% IACS.
2. The method for preparing a high-strength and high-conductivity graphene / copper composite material according to claim 1, characterized in that: In step S6, after the copper powder completely covered with graphene is subjected to hot pressing treatment, the graphene located between the copper powder particles is interconnected and presents a three-dimensional interconnected structure in the block, and the surface of the graphene / copper block obtained by hot pressing treatment has no pores or holes.
3. The method for preparing a high-strength and high-conductivity graphene / copper composite material according to claim 1, characterized in that: The purity of the copper powder is greater than 99.9%, the particle size of the copper powder is 15 μm-50 μm, and the input weight of the copper powder is 97-99% of the total weight of the mixed powder; The particle size of the graphite powder is 20 μm-50 μm, and the input weight of the graphite powder is 1% to 3% of the total weight of the raw materials composed of the mixed powder; The binder organic matter is selected from at least one of ethylene glycol, polypropylene glycol and polyethylene glycol, and the input weight of the binder organic matter is 10-20% of the total weight of the original solution composed of the mixed solution.
4. The method for preparing a high-strength and high-conductivity graphene / copper composite material according to claim 1, characterized in that: In the step S2, the binder organic substance is polyethylene glycol, the solvent is DMF, and the mass ratio of polyethylene glycol to DMF is 1:5-10; In step S3, the oxygen-containing groups include hydroxyl groups and carboxyl groups; In step S5, the reduction temperature of the reduction reaction is 250-450° C., the reduction reaction time is 0.5-1 hour, and the part of the graphene formed by the reduction reaction has wrinkles, and the Raman characteristic peak I of the graphene / copper composite material D / I G The ratio is 0.16-0.
18.
5. The method for preparing a high-strength and high-conductivity graphene / copper composite material according to claim 1, characterized in that: In step S3, the temperature in the hydrothermal reactor is controlled at 180-190° C., and the hydrothermal reaction is carried out for 10-15 hours. In step S5, the reduction temperature of the reduction reaction is 350° C. and maintained for 1 hour. In step S6, the graphene / copper composite material is subjected to vacuum hot pressing at a temperature of 800° C. for 2 hours.
6. The method for preparing a high-strength and high-conductivity graphene / copper composite material according to claim 1, characterized in that: In step S5, a mixed gas of nitrogen and hydrogen is used as a reducing atmosphere, wherein the volume percentage of nitrogen in the reducing atmosphere is 1-5%, and the temperature for the reduction reaction of the graphene oxide-coated copper powder composite material is 300-600° C. and the time for the reduction reaction is 30-200 min; In the step S6, the vacuum hot pressing temperature of the vacuum hot pressing treatment is 600° C.-1000° C., and the vacuum hot pressing time is 1-12 hours.
7. The method for preparing a high-strength and high-conductivity graphene / copper composite material according to claim 1, characterized in that: In the step S5, the temperature for the reduction reaction of the graphene oxide-coated copper powder composite material is 350° C. and the time for the reduction reaction is 60 min; In step S6, the vacuum hot pressing temperature of the vacuum hot pressing treatment is 800° C. and the vacuum hot pressing time is 2 hours; the periphery of the polycrystalline copper structure has 3-5 layers of graphene, and the graphene between each polycrystalline copper structure is interconnected to present a three-dimensional connected structure.
8. A high-strength and high-conductivity graphene / copper composite material, prepared according to any one of claims 1 to 7, characterized in that: The graphene / copper block exhibits a polycrystalline copper structure, showing Cu(111), Cu(200) and Cu(220) crystal plane indices. The bulk conductivity of the graphene / copper block is 97-107% IACS. The periphery of the polycrystalline copper structure has 3-5 layers of graphene. The graphene between each polycrystalline copper structure is interconnected and presents a three-dimensional connected structure.
9. The high-strength and high-conductivity graphene / copper composite material according to claim 8, characterized in that: Part of the graphene located at the periphery of the polycrystalline copper structure has wrinkles, and the wrinkles are graphene layers with 6-8 layers.
Citation Information
Patent Citations
Preparation and application of visible light responding CuAl2O4-graphene photocatalyst
CN102553591A
Graphene-supported copper-nickel composite nanometer photocatalyst, and preparation method and application thereof
CN104028272A
Graphene / copper composite and preparation method thereof
CN104711443A
